An assessment of the biological and socio-economic feasibility for successful culturing of the Iceland Scallop (Chlamys islandica) in the Westfjords of Iceland - Argue, David, 1973- (2018)
Due to exponential human growth over the last few decades, the Earth’s ecosystems are facing increasing pressure to feed the human population. Many species are being pushed to the brink of extinction due to the ever-increasing human appetite for food and living space. Since much of the world’s human population lives within easy access to the coastline, marine resources are being pushed to unsustainable levels to feed these populations. Most of the available land is either being used for residential or industrial purposes; and oceans, suffering from the effects of various forms of habitat pollution, are increasingly threatened as a food source. Many of the resources that the ocean produces are unable to overcome natural and man-made pressures, such as overfishing and habitat destruction that has led many to collapse. Aquaculture has the ability to reduce protein consumption pressure on capture fisheries for wild stocks, which has stabilised since the late 1980’s at approximately 90 million tonnes landed per year worldwide. The need for the global aquaculture industry to expand its capacity and current output of approximately 70 million tonnes per year, are paramount to feeding the world’s burgeoning population with a relatively cheap and affordable protein source. Aquaculture is a good way of alleviating this bottleneck, but it must be done in a sustainable manner so as not to put further stress on already over-burdened marine resources. Since the collapse of the scallop fishery in 2003, and the subsequent moratorium in 2004, there has not been any successful attempt at scallop aquaculture in Iceland since 1989-1993. This attempt was not successful as the cost was too high for equipment replacement due Iceland’s extreme weather patterns that were too much for the equipment to handle. An aquaculture venture in Iceland scallop farming should be of economic benefit to the Westfjords of Iceland, further increasing the financial capabilities of the municipalities in this area. A viable business opportunity here would ...